From Motherhood to Citizenship: Women's Rights and International Organizations - Abramovitz, Mimi (Hagar: Studies in Society and Culture, 2001)
The article reviews the book "From Motherhood to Citizenship: Women's Rights and International Organizations," by Nitza Berkovitch.